2020
DOI: 10.1101/2020.08.07.242271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 neutralization and serology testing of COVID-19 convalescent plasma from donors with non-severe disease

Abstract: We determined the antigen binding activity of convalescent plasma units from 47 individuals with a history of non-severe COVID-19 using three clinical diagnostic serology assays (Beckman, DiaSorin, and Roche) with different SARS-CoV-2 targets. We compared these results with functional neutralization activity using a fluorescent reporter strain of SARS-CoV-2 in a microwell assay. This revealed positive correlations of varying strength (Spearman r = 0.37-0.52) between binding and neutralization. Donors age 48-75… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…26 Other studies have demonstrated variable correlation between binding antibodies and neutralising antibodies, depending on severity of illness, but further evaluation is required. 27,28 In addition, the level of antibody required to result in protection is yet to be elucidated. Isolated reports of SARS-CoV-2 reinfection with genetically distinct strains have recently emerged.…”
Section: Discussionmentioning
confidence: 99%
“…26 Other studies have demonstrated variable correlation between binding antibodies and neutralising antibodies, depending on severity of illness, but further evaluation is required. 27,28 In addition, the level of antibody required to result in protection is yet to be elucidated. Isolated reports of SARS-CoV-2 reinfection with genetically distinct strains have recently emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous blood donor centers in the US implemented SARS-CoV-2 IgG antibody testing of blood donors in spring/summer 2020 to assist in the recruitment and collection of CCP. 11,[14][15][16][17][18][19][20] The FDA requires CCP to contain anti-SARS-CoV-2 antibodies; to ensure that the donors have sufficient antibodies, they must have had symptoms of COVID-19 and a positive test for COVID-19 or a reactive (positive) result in two different tests approved, cleared, or authorized by the FDA to detect SARS-CoV-2 antibodies. There is an additional recommendation to measure neutralizing antibody (nAb) titers if possible.…”
Section: Access and Regulatory Guidancementioning
confidence: 99%
“…21 Published data report that 82%-93.5% of donors with prior SARS-CoV-2 infection have demonstrable IgG antibodies with a positive correlation detected between the level of SARS-CoV-2 IgG antibodies and nAb titers. [14][15][16][17][18][19][20] A time-dependent decline has been shown in both nAb titers and detectable IgG in CCP donors and the general population post-infection. This may impact the maximum time a recovered person may donate CCP and also has important implications for durability of immunity.…”
Section: Access and Regulatory Guidancementioning
confidence: 99%
See 1 more Smart Citation